Tumor molecular differences associated with outcome disparities of Black patients with head and neck cancer. Issue 5 (21st February 2022) - Kim, Hugh A. J.; Zeng, Peter Y. F.; Sorgini, Alana; Shaikh, Mushfiq H.; Khan, Halema; MacNeil, Danielle; Khan, Mohammed I.; Mendez, Adrian; Yoo, John; Fung, Kevin; Lang, Pencilla; Palma, David A.; et al.
Abstract: Background: Numerous studies of head and neck squamous cell carcinoma (HNSCC) have demonstrated disparate outcomes by race and ethnicity. Beyond known associations with socioeconomic variables, whether these are also associated with differences in tumor molecular composition has thus far been poorly explored. Methods: We downloaded clinical and multiplatform molecular data from The Cancer Genome Atlas and other published studies. These were compared between non‐Hispanic Black ( n = 43) and White ( n = 354) patients with non‐HPV‐related tumors, using multivariable models. Publicly available validation cohorts were used. Results: Black patients had poorer progression‐free survival than White patients. Tumors of Black patients had greater copy number aberrations, and increased SFRP1 methylation and miRNA‐mediated PRG4 silencing associated with poor survival. PI3K/AkT/mTOR pathway proteins were differentially expressed. Conclusions: There are molecular differences between tumors of Black and White patients that may partially account for differences in survival. These may inform targeted treatment decisions to achieve equitable outcomes.